2018
DOI: 10.1016/j.jcis.2018.06.042
|View full text |Cite
|
Sign up to set email alerts
|

Studying the interaction of hydrophobically modified ethoxylated urethane (HEUR) polymers with sodium dodecylsulfate (SDS) in concentrated polymer solutions

Abstract: Binding of the SDS to the polymer via two mechanisms - monomeric anti-cooperative and micellar cooperative - leads to surfactant-concentration-specific macroscopic changes in the viscosity. Binding of the surfactant to the polymer drives a conformational rearrangement, and an associated redistribution of the polymer end-groups and linker associations throughout the hydrophobic domains. The composition and size of these domains are sensitive to the polymer architecture. Therefore, there is a complex balance bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…In the three cases, the solution viscosities were stable from pH 2.5 to 10 and from 0 to 1.2 wt % NaCl, highlighting very stable and versatile networks. Lately, Ibrahim et al 60 reported very interesting results about the interactions occurring between SDS and the urethane linkages of HEURs, a parameter always neglected in HEUR synthesis. They observed a higher viscosity for HEURs with higher urethane linkages content.…”
Section: Synthesis Of Heursmentioning
confidence: 99%
“…In the three cases, the solution viscosities were stable from pH 2.5 to 10 and from 0 to 1.2 wt % NaCl, highlighting very stable and versatile networks. Lately, Ibrahim et al 60 reported very interesting results about the interactions occurring between SDS and the urethane linkages of HEURs, a parameter always neglected in HEUR synthesis. They observed a higher viscosity for HEURs with higher urethane linkages content.…”
Section: Synthesis Of Heursmentioning
confidence: 99%
“…Therefore, the overall mechanical properties of the gel will be reduced. When the optimal concentration of SDS is reached, the network uniformity during gel polymerization is improved, the cross-linking density is stable, and the mechanical properties are enhanced. , With the further increase of SDS concentration, the stability of the network aggregation structure decreases. As the ratio of SA to AM increases, the chain entanglement in the self-healing gel network increases, thus enhancing the tensile strength of the rehealing.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4, shows the self-diffusion coefficient of HEUR in presence and absence of PS-BA-L. The polymer self-diffusion coefficients for the no-particle case have been taken from our previous study (32). One limiting case may be identifiedthat the polymer is completely adsorbed to the particle.…”
Section: Solution Polymer Aggregates In Presence Of Ps-ba-lmentioning
confidence: 99%